MEKANISME CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Ratnadewi, Putu Ari; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi, 2016)
This study was conducted to determine the effect of CSR disclosure on firm value and to determine the effect of Corporate Governance (CG) mechanism on the relationship between CSR and firm value. Purposive sampling is used to determine the number of samples in this study, resulting in 39 firms that met the criteria as the study sample. Secondary data as the source of the data used in this study of the annual reports of listed companies in Indonesia Stock Exchange for 2010-2012 and score CGPI obtained from SWA magazine. Data analysis was performed by descriptive analysis and Moderated Regression Analysis. The analysis showed that the first, CSR has a positive and significant effect on firm value. Second, the mechanism of CG has significant negative effect on the relationship between CSR disclosure and firm value.
Keywords: NP, CSR, CG